Assessing Ureteroscopy under General versus Spinal Anesthesia: Stone Clearance Success and Morbidity Outcomes - Muhammad Ejaz Siddiqui, Sana Atiq-Ur-Rehman, Ghulam Mustafa, Faisal Toheed, Syed Zamir-Ul-Hassan, Usman Zeeshan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Ureteroscopy is a common procedure for the management of ureteral stones, typically performed under either general anesthesia or spinal anesthesia. Objective: To compare the outcomes of these two anesthesia techniques in terms of stone clearance success, intraoperative hemodynamics, postoperative morbidity, recovery time, and postoperative pain management. Study design: Prospective observational study Place and duration of study: Department of Urology, Sir Ganga Ram Hospital Lahore from 1st January 2023 to 30th June 2023. Methodology: One hundred and thirty five patients were enrolled. Patients were randomly assigned to either the general anesthesia group (67 patients) or the spinal anesthesia group (68 patients). Stone clearance success, intraoperative hemodynamics, postoperative complications, recovery times, and pain scores were assessed and compared between the two groups. Results: Stone clearance success was 94% in the general anesthesia group and 95.6% in the spinal anesthesia group, with no significant difference (p=0.72). Intraoperative hemodynamic instability was observed in 12% of the general anesthesia group and 7.4% of the spinal anesthesia group (p = 0.35). Postoperative morbidity rates were 18% for the general anesthesia group and 14.7% for the SA group, with no significant difference (p = 0.58). Recovery time was significantly shorter in the spinal anesthesia group (45 minutes vs. 70 minutes, p<0.01). Postoperative pain scores were higher in the general anesthesia group at 1 hour (6.2±1.3 vs 5.1±1.2, p=0.03), but similar between the groups at 4, 8, and 24 hours. Conclusion: Both general and spinal anesthesia are effective for ureteroscopy, with similar stone clearance rates and low postoperative morbidity. However, spinal anesthesia offers a faster recovery time, which may be advantageous for patients seeking quicker discharge. While general anesthesia was associated with slightly higher immediate postoperative pain, pain management was comparable in both groups after the first hour. Both techniques are valid options, and the choice should be based on individual patient characteristics and clinical considerations. Keywords: Ureteroscopy, General anesthesia, Spinal anesthesia, Ureteric stones.